COMPUTATIONAL AERODYNAMIC STUDY OF A HATCHBACK CAR MODEL - Rio Teguh Kurniawan; Lavi R Zuhal; Ema Amalia (Mesin, 2008)
"Ahmed Body" is a well-established model of a hatchback car. In this study, computational simulations were conducted by using existing CFD software to capture "drag crisis" phenomena. Flow is assumed as incompressible flow with Reynolds Number of 4.3 x 10^6. A half of "Ahmed Body" was used in computational simulations with RANS method. Turbulence models that were employed mostly are k-e. The amount of grid cells used in computation is about 300.000. Computations were carried out mostly to get drag coefficients and also to examine vortex structure related to it. In "drag crisis" phenomena, maximum drag coefficient is reached at rear window angle of 30 degrees. Placement of spoilers and vortex generator has succesfully reduced the maximum drag coefficient at the critical angle of 30 degrees.